Influence of bone cement distribution on outcomes following percutaneous vertebroplasty: a retrospective matched-cohort study. Issue 7 (July 2021) - Mo, Ling; Wu, Zixian; Liang, De; Y, Linqiang; Cai, Zhuoyan; Huang, Jinjing; Lin, Shunxin; Cui, Jianchao; Zhang, Shuncong; Yang, Zhidong; Yao, Zhensong; Jiang, Xiaobing
Objective: To evaluate the influence of insufficient bone cement distribution on outcomes following percutaneous vertebroplasty (PVP). Methods: This retrospective matched-cohort study included patients 50–90 years of age who had undergone PVP for single level vertebral compression fractures (VCFs) from February 2015 to December 2018. Insufficient (Group A)/sufficient (Group B) distribution of bone cement in the fracture area was assessed from pre- and post-operative computed tomography (CT) images. Assessments were before, 3-days post-procedure, and at the last follow-up visit (≥12 months). Result: Of the 270 eligible patients, there were 54 matched pairs. On post-operative day 3 and at the last follow-up visit, significantly greater visual analogue scale (VAS) pain scores and Oswestry Disability Index (ODI) scores were obtained in Group B over Group A, while kyphotic angles (KAs) and vertebral height (VH) loss were significantly larger in Group A compared with Group B. Incidence of asymptomatic cement leakage and re-collapse of cemented vertebrae were also greater in Group A compared with Group B. Conclusions: Insufficient cement distribution may relate to less pain relief and result in progressive vertebral collapse and kyphotic deformity post-PVP.